30ft급 쌍동형 세일링 요트의 선체 유체력 계측에 의한 세일력 추정방법에 관한 연구 - 장호윤(Ho Yun Jang); 박충환(Chung Hwan Park); 김헌우(Hyen Woo Kim); 이병성(Byung Sung Lee); 이인원(In won Lee) (大韓造船學會 論文集, 2010)
During sailing by wind-driven thrust on the sail, a catamaran sailing yacht generates leeway and heeling. For predicting sail force, a model test was carried out according to running attitude. Through the model test, drag and side force of the real ship was predicted. A purpose of this study is to find sail force to C.E from changed attitude during running direction. By balance of hull and sail, a heeling force of designed sail is predicted. Also through heeling force and driving force, total sail force and direction from C.E are considered with changed mast including leeway and heeling.